Recent advances in the application of parahydrogen in catalysis and biochemistry. Issue 20 (26th April 2022) - Buntkowsky, Gerd; Theiss, Franziska; Lins, Jonas; Miloslavina, Yuliya A.; Wienands, Laura; Kiryutin, Alexey; Yurkovskaya, Alexandra
Abstract : This review provides a short introduction to the parahydrogen-based hyperpolarization (PHIP) techniques in NMR and MRI and then reviews the current literature on method developments and applications of various flavors of them. Abstract : Nuclear Magnetic Resonance (NMR) spectroscopy and Magnetic Resonance Imaging (MRI) are analytical and diagnostic tools that are essential for a very broad field of applications, ranging from chemical analytics, to non-destructive testing of materials and the investigation of molecular dynamics, to in vivo medical diagnostics and drug research. One of the major challenges in their application to many problems is the inherent low sensitivity of magnetic resonance, which results from the small energy-differences of the nuclear spin-states. At thermal equilibrium at room temperature the normalized population difference of the spin-states, called the Boltzmann polarization, is only on the order of 10 −5 . Parahydrogen induced polarization (PHIP) is an efficient and cost-effective hyperpolarization method, which has widespread applications in Chemistry, Physics, Biochemistry, Biophysics, and Medical Imaging. PHIP creates its signal-enhancements by means of a reversible (SABRE) or irreversible (classic PHIP) chemical reaction between the parahydrogen, a catalyst, and a substrate. Here, we first give a short overview about parahydrogen-based hyperpolarization techniques and then review the current literature on method developments and applications of various flavors of the PHIP experiment.